Processing factors affecting the level of residual cyanohydrins in gari - Onabolu, A.; Oluwole, O.; Rosling, H.; Bokanga, M. (Wiley, 2002)
Intake of cyanogens in gari, a food processed from cassava roots, is implicated in the causation of tropical ataxic neuropathy (TAN). This neurological syndrome is endemic in some communities in south‐western Nigeria. Studies have shown that methods of processing cassava roots determine the quantity of cyanogens in gari. This study was conducted to investigate the effects of the method of dewatering and the duration of fermentation on cyanogens in gari. Cassava roots (400 kg) were peeled, washed, grated and divided into 14 woven polyethylene sacks. The mash in seven of the sacks was dewatered continuously during fermentation, while the mash in the remaining seven sacks was fermented without dewatering, but dewatered at the end of fermentation. Cassava mash from each treatment was roasted into gari at 24 h intervals up to 168 h. Mean cyanohydrin content in gari roasted from cassava mash dewatered continuously during fermentation was 10.8 mg HCN eq kg−1 dw (CI 9.7–11.9), while mean cyanohydrin content in gari roasted from cassava mash dewatered after fermentation was 6.3 mg HCN eq kg−1 dw (CI 5.3–7.4). Mean linamarin content was 4.0 mg HCN eq kg−1 dw (CI 3.1–4.9) and mean HCN content was 1.6 mg kg−1 dw (CI 1.3–1.9) in gari roasted from cassava mash dewatered continuously, while mean linamarin content was 3.2 mg HCN eq kg−1 dw (CI 2.3–4.0) and mean HCN content was 1.2 mg kg−1 dw (CI 0.9–1.5) in gari roasted from cassava mash dewatered after fermentation. The method of dewatering cassava mash and the duration of fermentation were significantly associated with the level of cyanohydrin in gari (p < 0.001). This study shows that dewatering of cassava mash continuously during fermentation contributes to the dietary cyanide load in TAN‐affected communities.© 2002 Society of Chemical Industry